On Decolonising Revolution through a Lens of Afterlives - Alice Wilson (Práticas da História)
What do calls for decolonisation in postcolonial times offer to analysis of revolution? This article brings contemporary calls for decolonisation into conversation with scholarship on revolution. Taking inspiration from studies that question Enlightenment-centric paradigms of revolution, this article also understands decolonisation in postcolonial times as a project that contests ongoing colonial hierarchies, including violence, and retrieves the agencies that colonialist approaches neglect. Attending to these forms of decolonisation, first, the article outlines scholarship that decolonises ways of thinking about revolution, as a means of bringing visibility to those endeavours. Second, noting how this scholarship has prioritised events during or preceding revolution, the article extends inquiry temporally to address afterlives as a lens for decolonising revolution – and examines these possibilities through ethnographic work on the afterlives of revolutions that met with overwhelming repression, in Oman and beyond. Third, the article considers practical implications of decolonising analyses of revolutions and their afterlives.